Coronary artery disease in young adults: Angiographic study - A single-center experience - G Suresh; K Subramanyam; Srinivasa Kudva; Rama Prakasha Saya (Heart India, 2016)
Background and Objectives: Premature coronary artery disease (PCAD) seems to increase, particularly in developing countries. There are fewer data regarding myocardial infarction in young adults, with varying risk factors and patterns of coronary involvement. This study was done to present the coronary angiographic characteristics of CAD in young patients aged <40 years. Materials and Methods: In this cross-sectional record-based study, patients aged <40 years who were evaluated angiographically for chronic stable angina or acute coronary syndrome were included. Single vessel disease (SVD), double vessel disease (DVD), and triple vessel disease (TVD) were noted down. Onset of CAD before 40 years of age was considered as PCAD. Results: A total of 4526 cases underwent coronary angiogram between January 2008 and December 2014; 154 (3.40%) were <40 years of age with a mean (standard deviation) age of 36.51 (±3.654) years. In <40 years age group, nearly third-fourth of the cases (112, 72.73%) had critical CAD; among them, 98 (87.5%) were male and 14 (12.5%) were female. About two-third of the cases (74, 66.07%) had SVD, followed by DVD (25, 22.32%) and TVD (13, 11.61%). Conclusions: Incidence of critical CAD in young adults is quite high. Young patients with CAD are mainly males, and SVD is more common. Emphasis should be given on diagnosis and management of risk factors in this vulnerable group.